A non-systematic overview review of self-focused emotion regulation in autistic individuals through the lens of the extended process model - Cai, Ru Ying; Samson, Andrea C (Autism : the international journal of research and practice, 2025)
Difficulties regulating emotions have been coined as inherent to autism, possibly even presenting a core difficulty of autism. While several models of emotion regulation have been proposed in the past, in this targeted review article, we aim to map emotion regulation difficulties in autistic individuals within the framework of the extended process model of emotion regulation. This model can be considered the most comprehensive one currently incorporating not only different emotion regulation strategy groups but also different stages and processes involved in successful self-focused emotion regulation. Within this model, we will identify areas and domains as specifically impacted by autistic individuals. We will also outline gaps in the literature and provide suggestions for future research that can help deepen our understanding of the emotion regulation processes of autistic individuals. The ultimate goal is to develop specific support programs that address specific emotion regulation mechanisms, providing a much more individualized support approach. Lay abstract What do we already know about emotion regulation in autism? We know that many autistic children, youth, and adults experience difficulties regulating emotions. Existing research has focused mainly on the differences in emotion regulation capabilities between autistic and non-autistic individuals, the relationships between autistic traits and emotion regulation, and how emotion regulation relates to other outcomes, such as social skills and mental health. What does this paper add? We want to take a new approach to review the existing emotion regulation research through the lens of a specific theoretical model: the extended process model of emotion regulation. Professor James Gross developed this model. It consists of four emotion regulation phases: identification, selection, implementation, and monitoring. Our review revealed specific areas within these emotion regulation phases that could significantly impact the emotion regulation experiences of autistic individuals. We also outline the gaps in the research and propose avenues for future investigation. Implications for practice By deepening our understanding of emotion regulation in autistic individuals through the proposed future research, researchers and clinicians can pave the way for the development of tailored support programs. These programs will directly target specific emotion regulation mechanisms, offering a much-needed individualized support approach.